Penguatan Nilai Kewirausahaan di Unit Produksi Konsentrasi Keahlian Teknik dan Bisnis Sepeda Motor (TBSM) SMK Muhammadiyah 7 Gondanglegi - Ghulam Bahrudin (Jurnal Madani Mengabdi (JMM), 2025)
Entrepreneurship provides options for vocational school graduates to work directly or open new jobs through the entrepreneurial skills they have acquired at school. This community service activity was carried out at SMK Muhammadiyah 7 Gondanglegi located at Jl. KH. Ahmad Dahlan no. 20 Putat Kidul Gondanglegi, Malang, East Java 65174, Indonesia. The activity was carried out using lecture and discussion methods. The implementation of this activity was through lecture activities with discussion topics including entrepreneurial values in the production unit including self-confidence, independence, cooperation, search skills, action-oriented and communicative which were then continued with discussions. The conclusion of this community service activity was that there was a lecture on entrepreneurial strategies and the mentality that must be possessed by an entrepreneur to strengthen entrepreneurial values to students in the production unit with a concentration of motorcycle engineering and business expertise (TBSM) SMK Muhammadiyah 7 Gondanglegi.